2022
DOI: 10.1186/s12889-022-14350-y
|View full text |Cite
|
Sign up to set email alerts
|

’As safe as houses; the risk of childhood lead exposure from housing in England and implications for public health’

Abstract: Background and aim: Exposure to lead can harm a child's health, including damage to the nervous system, delayed growth, hearing loss, and many other adverse health effects, as well as implications for social, economic, educational and social well-being. Lead exposure in children is still a concern and cases require public health management to find the exposure source and interrupt the exposure pathway. Housing characteristics can indicate the presence of leadcontaminated paint and leaded water supply pipes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The association between lead exposure and social deprivation has also been seen in other populations [ 29 , 30 ]. However, some studies have not identified a relationship between IMD quintiles and BLC [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between lead exposure and social deprivation has also been seen in other populations [ 29 , 30 ]. However, some studies have not identified a relationship between IMD quintiles and BLC [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, where asked, 43% of cases knowingly lived in homes built before 1970, whilst 28% did not know and therefore, this percentage could be underestimated. Studies in England [ 31 ] and internationally [ 35 37 ] have identified housing age as a risk factor for lead exposure or higher BLC. Published literature tends to focus on household characteristics (age, type) as a proxy for exposure to household sources.…”
Section: Discussionmentioning
confidence: 99%